Reproductive Medicine in Ferrets - Jekl, Vladimir; Hauptman, Karel (The veterinary clinics of North America. Exotic animal practice, 2017)
In the United States, desexing is performed routinely in ferrets at the age of 6 weeks, therefore reproductive tract diseases are not so common. However, in Europe most ferrets are desexed when they are several months old, or they are kept as intact animals. For this reason, diseases of the reproductive organs and a prolonged estrus are far more frequent in Europe than in the United States. This article summarizes and reviews the anatomy, reproductive physiology, management of reproduction (including surgical and hormonal contraception) and reproductive tract diseases in male and female ferrets.
Keywords: Sterilization; Animals; Ferrets; rozmnožování; Female; ženské pohlaví; Reproduction; fretky; Hyperestrogenism; Contraception; estrus; Deslorelin; Ferret; reprodukční lékařství; Spojené státy americké; Male; Estrus; United States; Reproductive Medicine; mužské pohlaví; zvířata; Neoplasia